2007
DOI: 10.1089/aid.2007.0033
|View full text |Cite
|
Sign up to set email alerts
|

Failure of TLR4-Driven NF-κB Activation to Stimulate Virus Replication in Models of HIV Type 1 Activation

Abstract: The interaction of HIV-1 with Toll-like receptors (TLR) on host target cells is incompletely understood. Data from several in vivo and in vitro model systems suggest that TLR2, TLR4, and TLR9 remain functional and if stimulated, cause an upregulation of viral replication. In the present studies employing two different chronically HIV-1-infected cell lines and highly purified TLR agonists, we found ligation of TLR2 and TLR9, but not TLR4, resulted in significant upregulation of HIV-1 production. This result was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
6
25
0
Order By: Relevance
“…The pattern of IL-10 release was confirmed in clinically relevant human AMs, showing similar levels of lipid A-mediated IL-10 release comparing AMs from healthy persons to AMs from asymptomatic HIV ϩ persons ( Figure 2F). The observed differences in TLR4-mediated TNF␣ and IL-10 release were not related to differences in macrophage expression of essential TLR4 modulator molecule MD2 30 ( Figure 2G) or surface expression of TLR4 coreceptor CD14 ( Figure 2H), consistent with our prior studies showing similar TLR4 surface expression comparing U937 and HIV ϩ U1 macrophages 7,31 and comparing AMs from healthy and HIV ϩ persons. 8 In contrast to impaired TLR4-mediated MyD88-dependent release of TNF␣, collectively these data show that TLR4-mediated IL-10 and RANTES release in human macrophages is predominantly MyD88 independent and suggest that HIV may specifically target the MyD88-dependent TLR4 signaling pathway, while preserving the MyD88-independent TLR4 signaling pathway.…”
Section: Reduced Tlr4-mediated Tnf␣ Release Associated With Impaired supporting
confidence: 90%
See 1 more Smart Citation
“…The pattern of IL-10 release was confirmed in clinically relevant human AMs, showing similar levels of lipid A-mediated IL-10 release comparing AMs from healthy persons to AMs from asymptomatic HIV ϩ persons ( Figure 2F). The observed differences in TLR4-mediated TNF␣ and IL-10 release were not related to differences in macrophage expression of essential TLR4 modulator molecule MD2 30 ( Figure 2G) or surface expression of TLR4 coreceptor CD14 ( Figure 2H), consistent with our prior studies showing similar TLR4 surface expression comparing U937 and HIV ϩ U1 macrophages 7,31 and comparing AMs from healthy and HIV ϩ persons. 8 In contrast to impaired TLR4-mediated MyD88-dependent release of TNF␣, collectively these data show that TLR4-mediated IL-10 and RANTES release in human macrophages is predominantly MyD88 independent and suggest that HIV may specifically target the MyD88-dependent TLR4 signaling pathway, while preserving the MyD88-independent TLR4 signaling pathway.…”
Section: Reduced Tlr4-mediated Tnf␣ Release Associated With Impaired supporting
confidence: 90%
“…31,33 TLR4 is unique among the TLR family, supporting both MyD88-dependent and MyD88-independent signaling pathways, 11 whereas TLR3 exhibits MyD88-independent signaling, and all other TLRs exhibit MyD88-dependent signaling. 34 Activation of the MyD88-dependent signaling pathway promotes proinflammatory cytokine release such as TNF␣ and IL-12, 35 whereas activation of the MyD88-indepenent pathway promotes release of IFN-inducible genes such as type-1 IFN, IL-10, and RANTES.…”
Section: Discussionmentioning
confidence: 97%
“…6). An increase of TLR2, TLR4, and TNF-a in the H9 HTLV-IIIcc cells, a chronically infected cell line (data not shown), was observed, as also reported in U1 cells, 49 arguing that during chronic HIV-1 infection, proinflammatory cytokine release is increased.…”
supporting
confidence: 77%
“…These observations agree with the findings that HIV-1 infection itself leads to up-regulation of TLRs. 26 However, other authors have reported that TLRs signaling could be attenuated in HIV-1-infected cells, 48,49 although this was observed in a chronically HIV-1-infected cell line, that may contain some metabolic alterations affecting intracellular pathways. Likewise, it has been reported that HIV-1 and its products can also modulate TLR expression and functions.…”
Section: Discussionmentioning
confidence: 97%
“…TLR2 and TLR4 expressions are up-regulated after HIV infection. At the same time, high expression of TLR2 can promote HIV viral multiplication, but TLR4 expression has no such effect [19]. Therefore, TLR4 does not have any effects on HIV patients with TB, but TLR2 may play a key role in these patients.…”
Section: Cd4mentioning
confidence: 99%